2013
DOI: 10.1039/c3cc43161d
|View full text |Cite
|
Sign up to set email alerts
|

A bisphosphonate tweezers and clickable PEGylated PAMAM dendrons for the preparation of functional iron oxide nanoparticles displaying renal and hepatobiliary elimination

Abstract: The functionalization of superparamagnetic iron oxide nanoparticles (SPION) with PEGylated PAMAM dendrons through a bisphosphonate tweezers yielded 15 and 30 nm dendritic nano-objects stable in physiological media and showing both renal and hepatobiliary elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…[75] Bis [76,77,78,79,80] or tri-phosphonates [81] as well as multi-catechols [82,83,84] have been recently reported and stability studies under various conditions have shown that NPs functionalized with such molecules (carboxylic acid 75 or catechol 83 ) are more stable than the NPs functionalized with only one anchoring group. Because of their excellent complexing properties, bisphosphonates were evaluated as coupling agents to iron oxide NPs.…”
Section: Anchoring Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…[75] Bis [76,77,78,79,80] or tri-phosphonates [81] as well as multi-catechols [82,83,84] have been recently reported and stability studies under various conditions have shown that NPs functionalized with such molecules (carboxylic acid 75 or catechol 83 ) are more stable than the NPs functionalized with only one anchoring group. Because of their excellent complexing properties, bisphosphonates were evaluated as coupling agents to iron oxide NPs.…”
Section: Anchoring Groupsmentioning
confidence: 99%
“…Because of their excellent complexing properties, bisphosphonates were evaluated as coupling agents to iron oxide NPs. 78 Portet et al [85] have studied stabilizing compounds having different anchoring groups such as sulfates, carboxylates, and showed that the functionalization using bisphosphonates provides stable colloidal suspensions of NPs over a long period (4 weeks). Torres et al have coupled a radioactive label to a bisphosphonate molecule and have functionalized iron oxide NPs.…”
Section: Anchoring Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] However, MAG, used alone, is unstable in physiological media and needs a coated molecular layer to improve its biocompatibility, functionality, and stability. [4][5][6] One possible way to ameliorate these physicochemical factors is by loading iron oxide nanoparticles onto functionalized nanocarbons such as carbon nanotubes (CNTs) [7][8][9][10][11] and carbon nanohorns (CNHs). [12] Because of the exceptional combination of their mechanical, electronic, and thermal properties and chemical tolerance, nanocarbons are considered unique materials, with very promising future applications in a wide range of fields.…”
Section: Introductionmentioning
confidence: 99%